AP2/ERF Transcription Factor Regulatory Networks in Hormone and Abiotic Stress Responses in Arabidopsis - Xie, Zhouli; Nolan, Trevor M.; Jiang, Hao; Yin, Yanhai (Frontiers in Plant Science, 2019)
Dynamic environmental changes such as extreme temperature, water scarcity and high salinity affect plant growth, survival, and reproduction. Plants have evolved sophisticated regulatory mechanisms to adapt to these unfavorable conditions, many of which interface with plant hormone signaling pathways. Abiotic stresses alter the production and distribution of phytohormones that in turn mediate stress responses at least in part through hormone- and stress-responsive transcription factors. Among these, the APETALA2/ETHYLENE RESPONSIVE FACTOR (AP2/ERF) family transcription factors (AP2/ERFs) have emerged as key regulators of various stress responses, in which they also respond to hormones with improved plant survival during stress conditions. Apart from participation in specific stresses, AP2/ERFs are involved in a wide range of stress tolerance, enabling them to form an interconnected stress regulatory network. Additionally, many AP2/ERFs respond to the plant hormones abscisic acid (ABA) and ethylene (ET) to help activate ABA and ET dependent and independent stress-responsive genes. While some AP2/ERFs are implicated in growth and developmental processes mediated by gibberellins (GAs), cytokinins (CTK), and brassinosteroids (BRs). The involvement of AP2/ERFs in hormone signaling adds the complexity of stress regulatory network. In this review, we summarize recent studies on AP2/ERF transcription factors in hormonal and abiotic stress responses with an emphasis on selected family members in Arabidopsis. In addition, we leverage publically available Arabidopsis gene networks and transcriptome data to investigate AP2/ERF regulatory networks, providing context and important clues about the roles of diverse AP2/ERFs in controlling hormone and stress responses.